Budidaya Ubi Jalar Kaya Antosianin Model Pot Karung Vertikultur - Muhidin Muhidin; Dewi Nurhayati Yusuf; Sitti Leomo; Arsy Aysyah Anas; Gusti Ayu Kade Sutariati; Tresjia Corina Rakian; Waode Nuraida; Dedi Erawan (Jurnal Pengabdian Masyarakat Ilmu Terapan, 2022)
The sweet potato (Ipomoea batatas L). has significant potential as a source of carbohydrates in Indonesia The purple hue of sweet potatoes is a result of natural pigments known as anthocyanins. As antioxidants and free radical scavengers, anthocyanin chemicals have a crucial role in combating aging, cancer, and degenerative disorders. In addition, anthocyanins possess anti-mutagenic and anti-carcinogenic properties, as well as the capacity to prevent liver function abnormalities, act as antihypertensives, and reduce blood sugar levels. Given the numerous benefits of anthocyanin content, the presence of anthocyanin compounds as a source of natural antioxidants in purple sweet potatoes is highly intriguing. Alongside the growing public knowledge of healthy living, consumer food preferences are also altering. Foods that are beginning to be in high demand among consumers have an appealing appearance and flavor, as well as specialized physiological benefits for the human body. The presence of anthocyanin compounds in purple sweet potato makes this type of food very attractive to be processed into foods with functional value. On the one hand, with the increasingly limited land area, the potential for developing agricultural products, including sweet potatoes, is also increasingly limited. Meanwhile, on the other hand, the yard business model owned by households is not utilized optimally. Therefore, in providing healthy food and functional food based on anthocyanin-rich sweet potatoes, it is necessary to develop and revitalize yard land by vertically developing sweet potatoes in sacks. In addition to increase the availability of functional, healthy food, this activity is also a revitalization of the use of yardland.